DFT study on the effect of relative positions of methyl-, nitro- and N→oxide groups on the molecular structure, thermal/kinetic stability, crystal density, heat of decomposition and performance characteristics of triazolones. (18th July 2017) - Ravi, P.
ABSTRACT: Methyl-, nitro- and N→oxide substituted triazolones are of interest in the contest of high-energy density compounds and have been found to have true local energy minima at the B3LYP/aug-cc-pVDZ level. The optimised structures, harmonic frequencies and thermodynamic values for all the model molecules have been obtained in their ground state. The velocity of detonation (D) and detonation pressure (P) have been evaluated by the Kamlet–Jacob equations using the crystal density and the heat of explosion. The estimated performance properties are higher ( D  = 9.92–10.27 km/s, P  = 48.10–52.52 GPa) compared with 2, 4, 6, 8, 10, 12-hexanitro-2, 4, 6, 8, 10, 12-hexaazaisowurtzitane ( D  = 9.20 km/s, P  = 42.0 Gpa). The higher densities are possibly due to the intramolecular hydrogen bonds and the layered structures in the crystal lattice. We speculate that the calculated heat of explosion and the density are for the gas phase compounds and in the reality they should be for the solid phase which would diminish the magnitude of the calculated values. The –N→O and –NO2 group leads to the desirable consequences of higher heat of explosion and diminished sensitivities. The substituting of N–H hydrogen atom(s) of triazolones for a –CH3 group decreases melting point, heat of formation and density; however, the methyl group increases the thermal stability. Abstract :